Chronic Primary Headache Subjects Have Greater Forward Head Posture than Asymptomatic and Episodic Primary Headache Sufferers: Systematic Review and Meta-analysis - Elizagaray-Garcia, Ignacio; Beltran-Alacreu, Hector; Angulo-Díaz, Santiago; Garrigós-Pedrón, Miriam; Gil-Martínez, Alfonso (Pain medicine (Malden, Mass.), 2020)
Abstract Objective To summarize the cervical physical examination characteristics in subjects with chronic primary headache and compare those with a healthy population and a population with episodic primary headache. Design Systematic review and meta-analysis. Subjects Humans ≥18 years old. At least one of the study groups should be constituted by subjects diagnosed with one of the chronic primary headache subtypes according to the International Classification of Headache Disorders, 3rd Edition. Comparison Neck physical examination outcomes of subjects with chronic primary headache compared with a healthy population or subjects with episodic primary headache. Outcomes Forward head posture (FHP), cervical range of movement, motor control, neck muscle activity, and reproduction and resolution of symptoms. Methods Two reviewers assessed independently the MEDLINE, EMBASE, WOS, MEDES, PEDro, and CINAHL databases to select observational studies. First, both implemented an agreement for a search strategy. Then, they screened independently for duplicates, titles, abstracts, and full-text information. A meta-analysis was conducted to compare measures between groups. Results Twelve studies (N = 1,083) with moderate quality (mean ± SD = 7.75 ± 1.48 on the Newcastle Ottawa Scale) were selected for the qualitative analysis. The meta-analysis showed that patients with chronic primary headache presented greater forward head posture than asymptomatic participants (N = 275, Hg = 0.68, 95% CI = 0.25–1.1, Z = 3.14, P < 0.01) and patients with episodic primary headache (N = 268, Hg = 0.39, 95% CI = 0.13–0.65, Z = 2.98, P < 0.01). Conclusions There is moderate to strong evidence that patients with chronic primary headache present greater FHP than asymptomatic individuals and moderate evidence that patients with chronic primary headache present greater forward head posture than those with episodic primary headache.